Maternal Mental Health in Latinx/Hispanic Women after COVID-19 Pandemic - Gonzalez-Barrios, Polaris; Torres, Annelisse; Figueroa, Isel; Rosado-Abreu, Veronique; Rivera-Criado, Maria J.; Torres-Pérez, Jahleel; Kim, Sohye; Lugo-Candelas, Claudia; Buxó, Carmen J.; Martínez-González, Karen G. (Puerto Rico Health Sciences Journal, 2024)
The recent COVID-19 global emergency may have ripple effects on mental health of many people worldwide. This is especially true for populations like birthing and postpartum women where many changes to daily routines, access to medical care, work-related routines and socialization were experienced. This brief report presents data from an ongoing cohort study aiming to describe maternal mental health during the pandemic T12 (March 2020 to April 2021) with post-pandemic T2 (May 2022 to May 2023) of mothers followed in Puerto Rico. 47 out of 100 mothers have been recalled and assessed with psychosocial interviews (COPE-IUS) and assessments of anxiety (GAD-7) and depression (PHQ-9). Paired t-test revealed mean scores of depressions (PHQ-9) were significantly higher for T2 with a mean of 6.35 and a range of 4.4+/- than for T1 where mean was 5.15 (+/- 2.9), t=-1.954, df=45, p<.05. Similarly, anxiety scores (GAD-7) were significantly higher in T2 6.67 (4.2) than for T1 5.35 (3.7), t=-1.8, df=45, p<.05. Also, COPE-IUS Post-pandemic psychosocial interview results evidence that 80% of mothers do not feel the COVID-19 pandemic is a significant stressor at T2 and are able to maintain routine activities with no social distancing measures. However, reports of loneliness, sadness, worry, and fear continue to be present. Our findings point to the need to further identify other contributing factors to the deterioration of maternal mental health during the perinatal/peripartum period (pregnancy, birth, and postpartum) in Puerto Rico. Possibly the effects of repeated adversity that has been present in the island (multiple environmental stressors, history of traumatic experiences, and constant hardships) may all have cumulative impact over maternal mental health during the perinatal/peripartum period.